Pengaruh Shopee Live terhadap Peningkatan Penjualan: Studi Kasus Skincare Mia Glansie pada Februari 2024 - Yuliani, Agustina Lisa Tri (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This research aims to find out the influence of Shopee Live on increasing sales of Mia Glansie skincare products. The research method used is qualitative descriptive by analyzing sales data of Mia Glansie Skincare products in February 2024. Data is obtained directly from the source in the form of a table with 3 types of data, namely live orders, online orders, and offline orders which are made into graphs for comparison. The results of the study show that Shopee Live has a significant influence on the increase in sales of Mia Glansie Skincare products. This makes Shopee live very effective to support communication between sellers and buyers. This research has implications for online businesspeople to take advantage of the Shopee Live feature in increasing sales of their products.